Annual Trend of Myopia and High Myopia in Children in Japan: A Nationwide Claims Database Study - Kamei, Takuro; Miyake, Masahiro; Kido, Ai; Wada, Saori; Hiragi, Shusuke; Hata, Masayuki; Akada, Masahiro; Niimi, Koji; Ogino, Ken; Oishi, Akio; Nishida, Akihiro; Tamura, Hiroshi; et al. (Ophthalmology science (Online), 2025)
To determine the prevalence and annual trend of the number of incident cases of myopia and high myopia in children. A nationwide, comprehensive claims database study. Of 15 million children aged ≤14 years, those covered by the universal health insurance were included. The validation study of the claims-based definitions of myopia and high myopia was conducted using 14 654 individuals aged ≤14 years recruited from 11 diverse medical facilities. This study comprises a national claims database analysis and a multicenter validation study. Data from the National Database of Health Insurance Claims and Specific Health Checkups of Japan, which contains the nationwide health insurance claims data, were assessed. All individuals aged ≤14 years were reviewed, and children with existing and new onset of myopia or high myopia between January 2011 and December 2020 were identified. A validation study was conducted by reviewing electric medical records. Prevalence of myopia as of October 1, 2020, and the annual number of incident cases during 2014 to 2020. According to the 2020 population census, there were 14 955 692 children aged ≤14 years. Among them, 5 498 764 patients had myopia on October 1, 2020, corresponding to a prevalence of 36.8%. The number of incident cases of myopia was highest at 8 years of age, increasing from 853.3 cases/person-year in 2015 to 910.7 cases/person-year in 2020. The prevalence of high myopia increased with age, peaking at 0.46% among children aged 10 to 14 years; the number of incident cases annually increased in 5- to 9-year-olds and 10- to 14-year-olds. In the year 2020, when the coronavirus disease 2019 pandemic occurred, a discontinuous increase in the number of incident cases of myopia was observed in children aged 8 to 11 years, not 12 to 14 years. The overall sensitivity and specificity of the claims-based definition for myopia were 88.5% and 79.2%, respectively, whereas the corresponding values for high myopia were 41.6% and 99.8%. This first comprehensive nationwide study revealed the prevalence and annual incidence trends of myopia and high myopia. These findings complement the results of previous high-quality cohort studies, offering a more comprehensive understanding of myopia trends. Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.